(x',y')=A(x,y)
=matrix{(2,3),(3,-2)}(x,y)
=(2x+3y, 3x-2y)
つまり,(x',y')=(2x+3y, 3x-2y)より,
Aの逆行列をA'と置くと,
(x,y)=A'(x',y')
matrix{( -2, -3),( -3, 2) }
detA=-4-9=-13より,
∴A'=(-1/13){( -2, -3),( -3, 2) }
(x,y)=A'(x',y')より,
=(-1/13){( -2, -3),( -3, 2) }
=(1/13)( 2x'+3y' , 3x'-2y')
これをx^2 + y^2 = 13に代入すると,
(1/13)^2{ (2x'+3y')^2 + (3x'-2y')^2 } = 13
4(x')^2+9(y')^2 +6x'y' + 9(x')^2+4(y')^2 - 6x'y' = 13^3
13(x')^2 +13(y') = 13^3
(x')^2 +(y') = 13^2
∴半径√(13)円の方程式x^2+y^2=13は,
f(x,y)=(2x+3y, 3x-2y)の変換により,半径13の円となる.
----------------------------------------------------
以上です.